2007
DOI: 10.1136/gut.2006.117812
|View full text |Cite
|
Sign up to set email alerts
|

The T-box transcription factor eomesodermin controls CD8 T cell activity and lymph node metastasis in human colorectal cancer

Abstract: Background/aims: An efficient cytolytic T cell function is essential for immune mediated rejection of colorectal cancer. However, the molecular mechanisms driving T cell mediated cancer rejection are still poorly understood. Here, we assessed the relevance of the T-box transcription factor eomesodermin in colorectal cancer. Methods/results: By analysing tissue probes from 88 different colorectal tumours, a significant (p,0.02) inverse correlation between eomesodermin expression in colorectal cancers and the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 27 publications
1
36
0
Order By: Relevance
“…capacity determines the effectiveness of the immune system mediated tumor control was further supported by Atreya et al [46]. They showed that the expression of the T-box transcription factor eomesodermin, which is critically involved in controlling cytolytic activity of CD8+ T cells, inversely correlates to the occurrence of lymph node metastasis in CRC patients [46]. In contrast, Laghi et al [47] found that the density of CD3 + cells in the invasive margin of CRC could not be used as an independent predictor of survival, and at least for now, the TNM classification should remain the preferred prognostic system.…”
Section: Gene Expression Profiling and In Situ Ihcmentioning
confidence: 81%
See 1 more Smart Citation
“…capacity determines the effectiveness of the immune system mediated tumor control was further supported by Atreya et al [46]. They showed that the expression of the T-box transcription factor eomesodermin, which is critically involved in controlling cytolytic activity of CD8+ T cells, inversely correlates to the occurrence of lymph node metastasis in CRC patients [46]. In contrast, Laghi et al [47] found that the density of CD3 + cells in the invasive margin of CRC could not be used as an independent predictor of survival, and at least for now, the TNM classification should remain the preferred prognostic system.…”
Section: Gene Expression Profiling and In Situ Ihcmentioning
confidence: 81%
“…The data support the hypothesis that the adaptive immune response influences the behavior of human tumors. capacity determines the effectiveness of the immune system mediated tumor control was further supported by Atreya et al [46]. They showed that the expression of the T-box transcription factor eomesodermin, which is critically involved in controlling cytolytic activity of CD8+ T cells, inversely correlates to the occurrence of lymph node metastasis in CRC patients [46].…”
Section: Gene Expression Profiling and In Situ Ihcmentioning
confidence: 96%
“…Previous reports indicated a role of Eomes in the control of effector proinflammatory Th subsets. Gain-and loss-of-function experiments in both CD8 + (14,21,38,59) and CD4 + (8,11,22,40) T cells have shown that Eomes promotes cytotoxicity and IFN-g production in mice and humans. However, none of these settings showed essential functions of Eomes for the induction of IFN-g, probably due to compensatory effects of the related transcription factor Tbet (21,22,57).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the quality of T cells present within tumors is important for immune surveillance. Moreover, T-bet and Eomes were shown to be expressed in TILs of colorectal cancers, and the higher expression levels of these factors are correlated with better survival (7,20). T-bet-deficient mice are susceptible to prostate cancer metastasis (10).…”
Section: T-bet and Eomes Mediate Adaptive Immune Responses Against Camentioning
confidence: 99%